The Potential Ability of Plaster to Cause Breast Cancer as Indicated by CA15-3 and CEA Antigens in Women Working in Gypsum Factory - Ali Abdul Hussein S. AL-Janabi (Iranian Journal of Health, Safety and Environment, 2017)
Plaster is an important form of gypsum that mainly used in building construction. Breast cancer was investigated among women exposure to the dust of such material. The levels of CA15-3 and carcinoembryonic antigens (CEA) as indicators for breast cancer were measured in the serum of 120 women working in a plaster factory. All of involved women showed a normal level of CEA, while 12.5% of them had moderately elevated levels of CA15-3. In conclusion; plaster dust has no significant effect to cause breast cancer in working women. Moderately high levels of CA15-3 in some of exposed women may relate to liver diseases. Key words: Breast Cancer, Plaster, CA15-3, CEA